FACTORS AFFECTING WORK PERFORMANCE OF FAMILY PLANNING FIELD WORKERS OF NATIONAL AGENCY OF POPULATION AND FAMILY PLANNING (BKKBN) IN EAST JAVA PROVINCE, INDONESIA - Mahendrawan Nugraha Aji Pratama; Poschanan Niramitchainont (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: In a company or institution the most important asset is human resources. One of the functions of human resource management is training and development. The problem of family planning field worker in East Java Province that often faced is during the implementation of training activities, trainees showed high enthusiasm. However, based on data from BKKBN of East Java Province through Radalgram (program control meeting) in August 2018 explained that their performance achievements were still 73,41% of target more than 90%. This research was conducted at East Java Province to get an overview of the factors that affect the work performance of family planning field workers. Methods: The research design was a quantitative method used surveys. Measurement tool of this research is a questionnaire. The data were analyzed using descriptive statistics, Pearson’s Correlation, Stepwise Multiple Regression analysis. Results: Overall of the level of importance of factors affecting work performance of family planning of BKKBN in East Java Province, Indonesia were at high levels. The finding also revealed that there was a positive correlation between personal factor, training factors, organizational factors, and work performance. Teaching techniques had the highest influence on work performance, it could predict 38.6% of work performance. The second factor that effects work performance was self-directed learning which is could increase the prediction rate by 7.5 %. Furthermore, the third factor that affects performance isorganizational support, then the fourth and fifth factors are curriculum and training facilities that could increase the predictive rate of 3.7%, 1.8% and 1.0% respectively. Conclusions: Based on the result of this research, the highest influence factors to the work performance of family planning field workers of BKKBN in East Java Province, Indonesia are teaching techniques. The second highest factor is self-directed learning, then the third factor is organizational support. Other factors that affect performance in fourth and fifth are curriculum and training facilities. The researcher suggest that BKKBN pay more attention to facilitators so they can add competency in teaching, support family planning field workers by providing online learning programs and library. Moreover, BKKBN is expected to be able to make policies that provide fair assesment and appreciation for family planning field workers who have good performance. In addition, BKKBN should design a curriculum that is up to date and in accordance with the content of the training program, revitalizing training facilities in education and training center, so that family planning field workers are more comfortable to learn both independently and in groups. BKKBN expects that every family planning field workers to always learn independently and improve their competence in order to create innovative activities in carrying out work tasks in the area. Keywords: Family planning field workers, self-directed learning, training, perceived organizational support, work performance